Comparison of Measured and Computed Neutron Yield Versus Pressure Curve on NX2 at Different Operating Voltages - Gautam, Prakash; Khanal, Raju (Kathmandu University Journal of Science Engineering and Technology, 2014)
Numerical experiments are carried out using the Lee model code to compute the neutron yield of NX2 as a function of pressure. Results are compared with the published data (measured) and comparison shows good agreement for maximum neutron yield and for the range of the gas pressure. Measured neutron yield for operating voltage 14.5 kV is larger by factor 2 but operating voltages 10.5 kV and 12.5 kV is larger by more than factor 2.